Randomised, open-label, phase II study comparing the efficacy and the safety of cabazitaxel versus weekly paclitaxel given as neoadjuvant treatment in patients with operable triple-negative or luminal B/HER2-negative breast cancer (GENEVIEVE) - Kümmel, Sherko; Schneeweiss, Andreas (European journal of cancer, 2017)
Background: The GENEVIEVE study compared the pathological complete response (pCR) rate (ypT0/is ypN0/+) in patients with operable human epidermal growth factor receptor 2 (HER2)-negative breast cancer (BC) treated with either cabazitaxel or paclitaxel. Methods: GENEVIEVE was a prospective, multicentre, randomised, open-label, phase II study comparing the efficacy and the safety of four 3-weekly cycles cabazitaxel versus 12 weeks of paclitaxel given as neoadjuvant treatment. Primary end-point was the pCR rate defined as the complete absence of invasive carcinoma on histological examination of the breast irrespective of lymph node involvement (ypT0/is, ypN0/+) after the taxane treatment. Patients could receive an anthracycline-based therapy hereafter. Results: Overall, 333 patients were randomised and started treatment with 74.7% and 83.2% of patients completing treatment in the cabazitaxel and paclitaxel arms, respectively. Patients in cabazitaxel arm had a significantly lower pCR rate compared to the paclitaxel arm (1.2% versus 10.8%; p = 0.001). A total of 42 (25.3%) patients in the cabazitaxel arm and 17 (10.2%) in the paclitaxel arm had at least one serious adverse event (p < 0.001). Dose reductions were observed in 9.6% patients in the cabazitaxel arm compared to 11.4% in the paclitaxel arm (p = 0.721). Main reason for dose reductions was non-haematological toxicities in 3.0% versus 7.8% (p = 0.087), respectively. Conclusions: The GENEVIEVE study showed no short-term effect of cabazitaxel in triple-negative or luminal B/HER2-negative primary BC, while there seemed to be no differences in drug exposure and patient compliance between the two arms. Clinical trials registration ClinicalTrials.gov NCT01779479.
Gesehen am 27.11.2018